Content Analysis of the Book of Payāmhāye Āsemāni in the 1st Grade of High School Based on Consideration for Religious Sentiment - Abolfazl Nikounazar (پژوهش در آموزش معارف و تربیت اسلامی)
Religious sentiments have a determining role in the formation of students’ religious belief and upbringing. The educational system makes use of school curriculum to substantiate religious upbringing. In this regard, the purpose of the present research is to study components of religious sentiment within the books of Payāmhye Āsemāni in the 1st grade of high school. The research method is quantitative content analysis and the statistical population consisted of 3 volumes of Payāmhāye Āsemāni taught in 2022-2023. In order to choose the research sample, the survey method was used; therefore, the sample size was selected based on the statistical population. Data collection was conducted by research document and researcher made note of content analysis. To assess the validity of the research instruments, the ideas of experts in educational science were taken into account and the validity index was calculated to be 0.83 by Holsti formula. The results showed that two components of “affection to God” and “aversion to the enemies of God’s saints” have been considered by the authors more than other elements while consideration for some other components such as “affection to the saints and divine Imām” and “affection to the believers” has been less than expectation. Presentation of the content has been mostly through words and textual propositions while pictures were used less. The highest attention to religious sentiment was observed in the books of the 8th grade. According to the research results, it was determined that within the books of Payāmhāye Āsemāni, positive emotions have been considered by the authors more than the negative ones. Moreover, unbalanced distribution of components and lack of vertical relation in the arrangement of content were among some other results of the research.